2017
DOI: 10.1160/th17-03-0221
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Anti-PON1 and Anti-HDL Antibodies as Potential Biomarkers of Premature Atherosclerosis in Systemic Lupus Erythematosus

Abstract: The present study aimed to evaluate the possible role of immunoglobulin G (IgG) antibodies against high-density lipoproteins (HDL) and paraoxonase 1 (PON1) as possible biomarkers of cardiovascular disease (CVD) in systemic lupus erythematosus (SLE). To this end, levels of these autoantibodies, PON1 activity and total antioxidant capacity were quantified in serum samples from 198 SLE patients, 100 healthy controls (HC) and 42 non-autoimmune individuals with traditional cardiovascular risk factors. PON1 rs662 po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
25
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 64 publications
8
25
0
Order By: Relevance
“…Our findings revealed no association between anti-HDL and aCL antibodies, challenging the previous notion. This is in line with previous studies from our group when analyzing other disease-related autoantibodies positivity (8)(9)(10). Recent advances have brought to light the existence of a heterogeneous group of pathogenic autoantibodies in APS.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our findings revealed no association between anti-HDL and aCL antibodies, challenging the previous notion. This is in line with previous studies from our group when analyzing other disease-related autoantibodies positivity (8)(9)(10). Recent advances have brought to light the existence of a heterogeneous group of pathogenic autoantibodies in APS.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, although differences in hyperlipidemia were observed between patients and controls, the lack of association between lipid profiles and anti-HDL levels, and the relatively small differences in lipid levels between these two groups lead us to think that this do not represent a major limitation for our findings. This point is also supported by the existing literature findings (8,(39)(40)(41)(42)(43)(44). In summary, to the best of our knowledge, this is the first study informing an association between anti-HDL antibodies and thrombotic outcomes in APS patients.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…AAA patients are characterized by features of autoimmunity and lipid deposits in the wall of diseased aorta [20,21]. Emerging evidence from autoimmune diseases has revealed that the presence of autoantibodies directed against HDLc (IgG anti-HDL) may explain, at least in part, an impaired lipid profile in these conditions and they were associated with a number of disease outcomes [22][23][24][25]. Interestingly, similar results have been found in other non-autoimmune CVD conditions [26,27], hence suggesting that anti-HDL antibodies can be a common, shared mechanism across different conditions.…”
Section: Introductionmentioning
confidence: 99%